The Role of Media in Policy Communication for Flood Management in Banjarmasin City - Junaidy, Junaidy; Merdayanty, Dewi; Subhan, Rizky; DA, Elisa Oktaviani; Fadlun, Lukman; Anshari, Khairullah; Nasywa, Hanan (CV. Civiliza Publishing, 2025)
This study aims to analyze the role of media in the communication of flood management policies in Banjarmasin City, an area prone to flooding due to its geographical characteristics and rapid urbanization. Employing a descriptive qualitative approach, data were collected through in-depth interviews, focus group discussions (FGDs), and content analysis of local media coverage. The data were analyzed using techniques of data reduction, thematic categorization, and narrative interpretation. The findings reveal that the government's communication strategy remains predominantly top-down, relying heavily on digital media and technocratic narratives that are often difficult for the public to comprehend. Local media play a significant role in disseminating policy information but tend to favor government perspectives while providing limited space for civil society voices. The study also identifies several communication challenges, including unequal access to information, weak inter-agency coordination, and limited public dialogue. These findings highlight the need for a reformulation of flood policy communication strategies to be more dialogical, participatory, and community-based to enhance public awareness, preparedness, and active engagement in disaster mitigation.